In vitro activities of the multifunctional RNA silencing polymerase QDE-1 of Neurospora crassa. - Aalto, A; Poranen, M; Grimes, J; Stuart, D; Bamford, D (2010)
QDE-1 is an RNA- and DNA-dependent RNA polymerase that has functions in the RNA silencing and DNA repair pathways of the filamentous fungus Neurospora crassa. The crystal structure of the dimeric enzyme has been solved, and the fold of its catalytic core is related closely to that of eukaryotic DNA-dependent RNA polymerases. However, the specific activities of this multifunctional enzyme are still largely unknown. In this study, we characterized the in vitro activities of the N-terminally truncated QDE-1ΔN utilizing structure-based mutagenesis. Our results indicate that QDE-1 displays five distinct catalytic activities, which can be dissected by mutating critical amino acids or by altering reaction conditions. Our data also suggest that the RNA- and DNA-dependent activities have different modes for the initiation of RNA synthesis, which may reflect the mechanism that enables the polymerase to discriminate between template nucleic acids. Moreover, we show that QDE-1 is a highly potent terminal nucleotidyltransferase. Our results suggest that QDE-1 is able to regulate its activity mode depending on the template nucleic acid. This work extends our understanding of the biochemical properties of the QDE-1 enzyme and related RNA polymerases.